Socratic Method in the Active Learning of Philosophy of Education Students- UNSCH 2019 (Docentes 2.0 Journal, 2020)
The Socratic method or dialogue is a method of dialectic or logical parley for the investigation of new ideas or philosophical themes in general and of their disciplines. The present research was carried out with the objective of determining the influence of the Socratic method in the active learning of philosophy of the students of the Faculty of Education Sciences-UNSCH 2019. In this sense, an explanatory research with a quantitative approach was carried out in the paradigm positivist with experimental and comparative methods to determine the influence of an independent variable on another dependent variable. The Socratic method in the active learning of philosophy, whose geographical space corresponds to the Faculty of Education Sciences of the National University of "San Cristóbal de Huamanga", said sample was made up of 48 students from the Professional School of Initial Education of said Faculty of series 100 or first year, curiously made up of only women, forming two groups at the discretion of the researcher: one control and the other experimental. The results refer after applying the Socratic method to the experimental group, the average index of active philosophy learning significantly increased compared to those who were not exposed to this method. In conclusion, the Socratic method significantly influences the active learning of philosophy in the experimental group compared to the control group who do not apply this method in the Faculty of Education Sciences, according to the universal statistical parameter "T" of Student (?
Keywords: Socratic method; active learning; philosophy